Pengaruh Service Quality Terhadap Repurchase Intention Dengan Customer Satisfaction Sebagai Variabel Intervening Pada PT Bank Central Asia Tbk. Studi Kasus KCU Darmo Surabaya - Yohan Tan (Jurnal Strategi Pemasaran, 2019)
The influence of Service Quality on Repurchase Intention with Customer Satisfaction as an intervening variables at PT Bank Central Asia Tbk. Case Study of KCU Darmo Surabaya. Users of bank accounts begin to increase every year, one of them in Surabaya. With the rapid development of technology, the ease of conducting transactions is one of the reasons why many people decide to open savings accounts with the Bank This research aims to analyze the influece of Service Quality (Reliability, Responsiveness, Assurance, Empathy and Tangible), to Repurchase Intention (Social Factor, Psychological Factor) with Customer Satisfaction (Attributes related to product, Attributes related to service, Attributes related to purchase) as an intervening variables at PT Bank Central Asia Tbk. Case Study of KCU Darmo Surabaya This research was conducted by distributing questionnaires to 105 respondents customers of PT Bank Central Asia Tbk. Analytical technique used in technical quantitative analysis with path analysis method.